Life Cycle Assessment Based Analysis of Water Bottle Designs for Defence Application - Pandey V.S.; Agrawal A.K.; Dubey A. (My University, 2025)
This paper presents the successful implementation of the Life Cycle Assessment (LCA) approach for the sustainable development of a defence product. Alternative designs of this product are evaluated from the environmental burden perspective. The products considered are water bottles used by the armed forces in places like the Siachen glacier, where environmental factors are of great concern. From the environmental degradation perspective, the suitability of three existing bottle types has been analysed using LCA and Life Cycle Impact Assessment (LCIA) approaches on SimaPro software for each of its components and the bottle as a whole. Using this software, uncertainty analysis has also been carried out by conducting a Monte Carlo simulation for a reasonable confidence level. The latest design was found to have the least environmental burden, being 82.62 % less compared to the first design. To augment the environmental performance further, the best design was again reviewed by carrying out component-level analysis to identify feasible alternative materials that would be functionally equivalent but with lower environmental impact. It suggested switching to lower impact material for the cap and cap cover for the proposed design. With the adoption of the changed material, the environmental performance improved by 10.61 per cent as compared to the best design and 84.46 per cent compared to the earliest design. © 2023, DESIDOC.